Electrochemical characterization and calculation methods of supercapacitors - Teo, Ellie Yi Lih; Chong, Kwok Feng (Elsevier Inc., 2024)
As the demand for clean energy increased exponentially over the last decade, the spotlight is also on energy storage devices as they play a major role in supporting the deployment of renewable energies. Supercapacitor, an electrochemical energy storage device that is well known for its high power density and long life cycle has attracted much research interest. To increase the applicability of supercapacitors in various fields, researchers have continuously worked to improve the performance of the device through the advancement of various components (electrode material, electrolytes, separator, etc.). The performance of supercapacitors is characterized via several electrochemical methods such as cyclic voltammetry, galvanostatic charge–discharge, and electrochemical impedance spectroscopy. Data obtained from the electrochemical measurements enable parameters such as specific capacitance, power density, and energy density to be determined. Appropriate characterization and data evaluation are necessary to facilitate the development of supercapacitors to be effective energy storage devices. In this chapter, we present the key electrochemical characterizations performed on supercapacitors, interpretation of data obtained from the characterizations and recent literature.